Social Cohesion in International Comparison: A~Review of Key Measures and Findings - Jan Delhey; Georgi Dragolov; Klaus Boehnke (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Although social integration has always been a~central sociological issue, there has never been a~consensus how to approach the topic empirically. In the new millennium, social cohesion has emerged as a~lead concept for measuring how integrated societies are—not the least, because many observers see the social fabric of modern-day societies in deep crisis. Consequently, scholars and think tanks have intensified their efforts to chart how strong the social glue of contemporary societies is, as well as which conditions strengthen or weaken it. The main goal of our article is to provide an overview of measures of social cohesion that have been specifically designed for cross-national comparisons. To this end, we compare selected measures with respect to what they measure, how, and for what purpose. We then highlight key empirical insights gained by these measures, touching upon the issues of levels, regimes, as well as determinants and outcomes of social cohesion. The review concludes that one of the measures, the Bertelsmann Social Cohesion Radar, stands out in terms of conceptual clarity, methodological sophistication, and richness of empirical findings.
Keywords: 300; Cohesion measurement; Composite index; Cohesion regimes; Social Cohesion Radar; World regions; Messung von Zusammenhalt; Gesamtindex; Indikatoren; Internationaler Vergleich; Weltregionen